Diabetes mellitus type 1 in childhood - Ertu?rul, Sebahattin; Yilmaz, Erdal; Aydin, Mustafa; Taşkin, Erdal; Özcan, Kenan (My University, 2006)
Diabetes mellitus is a chronic endocrine and metabolic disease; characterized by hyperglycemia due to deficiency of either insulin secretion or insulin effect, causes severe complications in the long term. Insulin is a hormon synthesized at beta cells of pancreas and controls energy homeostasis. Either relative or absolute deficiency of insulin causes impairment of carbohydrate, lipid and protein metabolism. Although all of the diabetes subgroups (except gestational diabetes) classified by American Diabetes Association can be seen in childhood, more than 95% of diabetic cases have type 1 diabetes that is characterized by insulin deficiency.
Çocukluk ça?inda diabetes mellitus tip 1
Keywords: insulin; article; chronic disease; clinical feature; diabetes mellitus; disease classification; disease severity; disorders of amino acid and protein metabolism; disorders of carbohydrate metabolism; disorders of lipid and lipoprotein metabolism; energy balance; heredity; human; hyperglycemia; insulin deficiency; insulin release; insulin synthesis; medical society; pancreas islet beta cell; pathogenesis; pathophysiology; prevalence; United States